FREQUENCY OF SENSORY SIGNS AND SYMPTOMS IN GUILLAIN BARRE SYNDROME PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL. - Ghulam Mujtaba1, Aijaz Ali2, Awais Bashir3, Ameet Kumar4, Dileep Kumar5, Kashaf Anwar6., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
OBJECTIVE: To determine the frequency of sensory signs and symptoms in GBS (Guillain Barre Syndrome) patients, presenting to a tertiary care hospital. DESIGN: Descriptive cross sectional study PATIENTS AND METHODS: This study was conducted in department of Neurology, Jinnah Postgraduate Medical centre, Karachi. Total of 105 GBS diagnosed cases were included in this study. A thorough history was taken. The focus was on presence of sensory signs and symptoms in GBS patients and all the information was entered in the proforma. RESULTS: There were 60(57.14%) male and 45(42.86%) female. Sensory symptoms were widely prevalent pain 44.8%(47/105), paresthesia 81%(85/105), impaired pain and temperature sensation, 26.7%(28/105), impaired joint sensation 28.6%(30/105), impaired vibration sensation 22.9%(24/105) and electrophysiological sensory abnormalities 59%(62/105). CONCLUSION: Pain in GBS is an important treatable symptom which is often overlooked. Tactile appearances in GB disorder are regularly under-perceived and under-stressed. This examination broke down the development and the profile of agony and paresthesia in GB disorder during hospitalization. Information, particularly about development of torment and paresthesia during hospitalization may improve understanding and patient consideration.